La Cité des Roms . City of the Roma - Castaignède, Frédéric (France, 2008)
Donation from OSI-Budapest Arts and Culture Program. Duration: 01:37:00 Nadezhda, in the town of Sliven in Bulgaria is one of the biggest Roma ghettos in Europe. 20,000 people live packed into an unsanitary environment, walled off from the city by a three metre high wall. Nadezhda itself is a symbol of the apartheid that most Roma suffer from in Europe today. A glimmer of hope exists through education between the segregated schools in the ghetto and the rare few that welcome Roma children on the outside.